Magnetron with a concave hemispherical cathode - Stetsenko, B.V.; Shchurenko, A.I.; Zavyalov, Yu.G. (Вопросы атомной науки и техники, 2009)
A magnetron set up with a hemispherical concave cathode has been worked out for the first time. The cathode
center of curvature was registered with the sputtered surface. An aluminum nitride film was sputtered by this magnetron
in the pulse regime. The pulse duration was about 2 ms. The film thickness was between 10 to 12 nm. The sputtering
rate was about 50 nm/s. The magnetron characteristics agree with a qualitative model of the magnetron. Вперше створено модель магнетрону з напівсферичним катодом, що увігнутий у бік поверхні, на яку
проводиться напорошення. В імпульсному режимі напорошена плівка нітриду алюминию, товщина якої в
центрі запорошеної області дорівнює 10 нм, а поблизу края катоду – 12 нм. Швидкість запорошення − 50 нм/с.
Характеристики магнетрону якісно відповідають модельним розрахункам. Впервые создана модель магнетрона с полусферическим катодом, вогнутым в сторону напыляемой
поверхности. В импульсном режиме напылена плёнка нитрида алюминия, толщина которой в центре
запыленной площадки равна 10 нм, а вблизи края катода − 12 нм. Скорость напыления − 50 нм/c.
Характеристики магнетрона качественно соответствуют модельным расчётам.